A democracia deliberativa na teoria Habermasiana: limites e possibilidades à luz da cultura contemporânea - Weber, Josnei Machry (2018)
Modernity, as conceived by the illuminists ideals, is in threat. The founding assumptions of the modern project, such as objectivity, rationality and, consequently, and of paramount importance, human emancipation, would be threatened by factors such as individualization, subjectivation, and depoliticization. This research, based on these questions, makes the relation between two thinkers who have in modernity and their sociopolitical and cultural unfolding their privileged objects of analysis; namely Habermas and Bauman. This study therefore has as its central focus the objective of analyzing the possibilities and especially the limits of the deliberative models of democracy (markedly derived from the Habermasian theory) before a (Baumanian) diagnosis of increasing individualization and subjectivation of contemporary society, which has depoliticization as one of its main characteristics. Are deliberative/ participatory models of public management feasible if, at the present time, the "citizen" that this model presupposes - and of which it needs to function - is something in extinction? The research is qualitative in the sense that it will be constituted by means of a theoretical investigation based on the content analysis of the theoretical works of the thinkers, with exercise of confrontation of the two authors, aiming to point out limits to the consequences of a theoretical model from of the reflections of another. Because of that, it is also a necessarily bibliographical research. What has been perceived with the development of this research is that the Baumanian diagnosis of liquid modernity deals with the fluidity and transience of relations as corporate premises, thus determining an individual who is an enemy of the citizen. The consumer, in this sense, takes the place of the citizen, and the economic / market aspect takes the place of the political dimension in society. The idea of citizenship, associated with participation in political life, is replaced by a conception of citizenship based on consumption. In other words, the depoliticization aspect of liquid modernity involves several dimensions, but within the scope of this work the subjectivation aspect and its consequent irrationalism as an element of contradiction with the Habermasian perspective, which, still modern, is still centered on rationality. It was not, however, a question of saying that Bauman is against Habermas, but of assuming that his diagnosis of contemporary society can contribute to the thinking of the operational limits of deliberative democracy in the Habermasian mold. Once, in spite of the fact that the deliberative proposal of democracy based on Habermasian communicative action is structured from the perspective of a pragmatic discourse, this model needs, in order to function, citizens who are minimally prepared and motivated to deliberate about the public sphere. It was observed, however, that even the Habermasian model lacking the oxygen that would make him breathe, which is the citizen (in the modern molds), this is necessary in the way of critical questioning of the existing forms of interaction and discourse, because it refers to a normative and social reflection - with an emancipatory bias through the development of a universal moral conscience - about the possibility of the realization of new forms of democracy.